Probiotic Potential Of Lactic Acid Bacteria From Fermented Malaysian Food Or Milk Products - Nor Zaihana Abdul Rahman; Kalavathy Ramasamy; Sieo Chin Chin; Nur Jahan Alitheen; Norhani Abdullah; Ho Yin Wan (Institute of Food Science & Technology, 2024)
This study investigated the probiotic characteristics of lactic acid bacteria (LAB) isolated from 14 Malaysian fermented food or milk products. In total, 22.3% (121 of 542) of the LAB isolated from the local fermented products exhibited antibacterial activity against Micrococcus luteus. Twelve LAB that demonstrated better antibacterial activity against M. luteusas compared to a commercial strain Lactobacillus case istrain Shirota(LABPC) were selected for further characterisation. Based on 16S rRNA gene sequence, the LAB were identified as pediococci (seven) and lactobacilli (five). All 12 LAB showed bile tolerance, but only eight were acid tolerant at pH‡3.0. The highest level of adhesion to HT-29 cells was observed among the Lactobacillussp. LAB 1 and 10. The LAB also showed antimicrobial activity against Escherichia coli and Staphylococcusaureus through the production of organic acids. LAB isolated from Malaysian fermented food and milk products, especially fermented tapioca, contains potential probiotic candidates.